[View of the exterior of Kennedy Library under construction] - P. K. Phillips::::::photographer::: (1978)
View of the exterior of Kennedy Library, under construction. This image was captured facing the main entrance to the building. Mobile homes utilized by the workers are visible, along with the equipment and materials used on the project.